(untitled) (Portuguese Journal of Family Medicine and General Practice, 2003)
In daily practice strange situations of difficult understanding sometimes pop up, the patient doesnt help and investigations do not seem to be on our side. All possibilities, even the most unbelievable, must be considered in order to have a solution. We describe the case of a vaginal foreign body that, after pathology analysis, was found to be bone fragments, probably the result of post abortion retention. Though described in the medical literature, this is a rare situation, namely because of the vaginal location of these fragments.